Staged approach to bilateral severe carotid stenosis: a case report and literature review - Frade, Heitor Cabral; Kaur, Manmeet; Aigbogun, Julia; Memon, Muhammad Zeeshan; Chhabra, Arun; Muktadir, Akm; Shaltoni, Hashem (Frontiers in Stroke, 2025)
IntroductionCarotid atherosclerotic disease (CAD) is a major cause of stroke, often requiring a combination of medical and surgical interventions. Current guidelines have established well the role of interventions such as carotid endarterectomy and carotid artery stenting (CAS) for unilateral carotid disease. However, there is still a paucity of evidence on the timing, procedural order, and complication rate of these procedures when there is bilateral carotid involvement. Hyperperfusion syndrome (HPS), with or without associated intracerebral hemorrhage, although rare, is a major source of morbidity and mortality after carotid interventions, especially in the setting of bilateral CAD. In select cases, staged bilateral CAS (BCAS) appears to attenuate periprocedural risks, including HPS.Case reportA 62-year-old male presented with acute dysarthria and right-sided face and upper extremity weakness, amounting to an initial National Institutes of Health Stroke Scale (NIHSS) score of 6. Emergent neuroimaging revealed a dense left MCA sign, complete occlusion of the left proximal internal carotid artery (ICA), and severe stenosis of the contralateral ICA. The patient received intravenous thrombolysis and underwent perfusion imaging for possible mechanical thrombectomy. Although the imaging was favorable for endovascular recanalization, the patient continued to clinically improve to an NIHSS score of 3 during angiography, which showed interval recanalization of left proximal ICA, so the procedure was aborted in favor of a delayed staged BCAS. On the day of the first procedure, angiography revealed interval recanalization of the distal ICA and collateral flow to the middle cerebral artery territory associated with early hyperemia. The risks of symptomatic CAS in light of these findings were discussed with the patient, and a shared decision was made to first pursue endovascular treatment of the asymptomatic severe right CAD, followed by treatment of the symptomatic left CAD, to avoid periprocedural complications such as HPS. The patient continued to improve clinically after both procedures and was able to attain functional independence and resume all previous activities following interventions.ConclusionThis case and literature review suggest that, although both simultaneous and staged BCAS may be feasible treatment options for bilateral CAD, staged BCAS appears to have fewer periprocedural complications such as HPS.